2010
DOI: 10.1159/000277589
|View full text |Cite
|
Sign up to set email alerts
|

Lowering the PSA Threshold for Prostate Biopsy from 4 to 2.5 ng/ml: Influence on Cancer Characteristics and Number of Men Needed to Biopt

Abstract: Objective: In 1999 we lowered the prostate-specific antigen (PSA) threshold for prostate biopsy at our institution from 4 to 2.5 ng/ml. The aim of this study was to compare the differences in tumor characteristics of the detected prostate cancers (PCAs) and the detection rate for the two different PSA thresholds and to evaluate if lowering the threshold was justified by any of the detected differences. Patients and Methods: We retrospectively analyzed the records of all patients who underwent an 8-core prostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In general, a PSA level of > 4 ng/ml is considered abnormal. Over the past few decades, it was reported that prostate malignancy with a PSA concentration of below 4.0 ng/ml was not rare, with the detection rate of PCa ranging from 17% to 32% ( 14 16 ). However, few studies have reported the possibility of other malignant outcomes in biopsy patients with low PSA levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, a PSA level of > 4 ng/ml is considered abnormal. Over the past few decades, it was reported that prostate malignancy with a PSA concentration of below 4.0 ng/ml was not rare, with the detection rate of PCa ranging from 17% to 32% ( 14 16 ). However, few studies have reported the possibility of other malignant outcomes in biopsy patients with low PSA levels.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some published reports now support a PSA threshold of 2.5 ng/ml for recommending prostate biopsy ( 6 , 16 , 18 ). However, in this study, there was no significant difference in the detection rate of prostate adenocarcinoma and all prostate malignancies between the 0.0–2.5- and 2.6–4.0-ng/ml groups.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that lowering the PSA cutoff value from 4 to 2-3 ng/mL is appropriate because high PCa detection rate is demonstrated in those range of PSA. PSA cutoff value from 4 to 2.5 ng/mL results in an increase in the number of men who undergo biopsy and may result in an increased detection of potentially insignificant PCa 12. The adequate PSA cutoff value for prostate biopsy remains controversial.…”
Section: Discussionmentioning
confidence: 99%